ANALISIS YURIDIS PERUBAHAN PERATURAN PENANAMAN MODAL ASING DALAM UU CIPTA KERJA NO 11 TAHUN 2020 PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU -XVIII/2020 - NIM. A1011191029, FLORENTINUS ELVIN (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstract Omnibus law is a technique/method of formulating statutory norms through one new legislation correcting many laws simultaneously to achieve very important government policies.The type of legal research used in this research is normative legal research which will be presented through analytical descriptive with a normative juridical approach and concepts,perspectives, theories from experts. The results of this study show that the Job Creation Law remains in effect and Foreign Investment in Indonesia has legal certainty and that Foreign Investment activities in Indonesiacontinue as it should with the Job Creation Law.Keywords: Omnibus law, Foreign Investment, Investment ABSTRAK Omnibus law merupakan teknik/metode perumusan norma peraturan perundang